Development of Anthelmintic Resistance Detection Methods of Gastrointestinal Nematodes on Livestock - Haryuningtyas, Dyah (Indonesian Animal Sciences Society, 2008)
The intensive usage of anthelmintic in most of farms led to resistances of livestock gastrointestinal nematodes against anthelmintic. Many reports of resistance that increased every year happen following the continuing helminth control programmes. The succesful implementation of helminth control programmes that designed to minimize the development of resistance in nematode populations depends on the availability of effective and sensitive method for its detection and monitoring. A variety of in vivo and in vitro tests have been developed for detecting nematode population resistance to the main anthelmintic groups. This paper will discuss the development of detection method of anthelmintic resistance based on conventional and molecular approach according to their strengths and weakness. Key words: Anthelmintic resistance, detection method, conventional, molecular, nematode